2017
DOI: 10.1002/dmrr.2926
|View full text |Cite
|
Sign up to set email alerts
|

The association between dysregulated adipocytokines in early pregnancy and development of gestational diabetes

Abstract: Decreased high molecular weight adiponectin and omentin-1 and increased IL-6 may enhance sensitivity of early risk prediction tools for women at high risk of GDM. This may allow early identification and opportunities for prevention of GDM and adverse outcomes. Further research is required in large validation studies to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 35 publications
1
23
1
16
Order By: Relevance
“…Two prior studies have reported significantly higher IL-6 concentrations at 11–15 GWs among women who subsequently developed GDM. 36 37 However, in other small studies with less than 30 GDM cases the higher IL-6 concentrations among GDM cases were not statistically significant. 38–40 Our data provide the first report of longitudinal profiles of IL-6 throughout pregnancy by GDM status among a larger racially/ethnically diverse sample.…”
Section: Discussionmentioning
confidence: 79%
“…Two prior studies have reported significantly higher IL-6 concentrations at 11–15 GWs among women who subsequently developed GDM. 36 37 However, in other small studies with less than 30 GDM cases the higher IL-6 concentrations among GDM cases were not statistically significant. 38–40 Our data provide the first report of longitudinal profiles of IL-6 throughout pregnancy by GDM status among a larger racially/ethnically diverse sample.…”
Section: Discussionmentioning
confidence: 79%
“…The present review also included studies that did not show a correlation between the serum levels of IL-6 and GDM, such as the study conducted by Abell et al [ 24 ], which aimed at evaluating the relationship between GDM risk using fasting glucose and serum biomarkers at the early pregnancy, and indicated that the serum IL-6 levels did not improve the ability to predict the risk of GDM. The results of another study conducted by Gümüş et al [ 29 ] aimed to evaluate the possible association between clinical and biochemical parameters with GDM and gingivitis; this study showed that there was no association between the serum IL-6 levels and GDM.…”
Section: Discussionmentioning
confidence: 99%
“…However, no difference was indicated in obese women with GDM and normal glucose tolerance [71]. It was shown that omentin-1 concentrations lower than 38 ng/ml are associated with a 4-fold greater risk of developing GDM [67]. In a prospective study of pregnant women during the second and third trimesters, no significant differences in omentin-1 levels in the plasma of healthy women and those with GDM were identified.…”
Section: Factors Affecting Insulin Resistance In Pregnancymentioning
confidence: 99%
“…Its concentrations are lower in people with insulin resistance, i.e. those suffering from obesity, type 2 diabetes, PCOS, and GDM [67][68][69]. The highest adipokine concentrations in pregnant women were observed during the first trimester and they decreased during the second trimester [70].…”
Section: Factors Affecting Insulin Resistance In Pregnancymentioning
confidence: 99%